Entrepreneurial Innovation and Leadership Preparing for a Digital Future (Springer International Publishing, 2018)
'Drawing on current experiences of start-ups, supporting institutions and established firms, the cross-disciplinary team of contributors provides a challenge for academics, practitioners and policymakers seeking to create an environment supportive of both incremental and radical innovation.' Stephen E. Little, Asia Pacific Technology Network UK 'This is an interesting and timely text concerning entrepreneurial behaviour in relation to the increasingly important areas of radical and disruptive innovation in the rapidly expanding digital market space.' Ian Chaston, Professor, University of Auckland, New Zealand Taking the themes of entrepreneurship, start-ups, innovation and collaboration, this book seeks to answer the urgent question of how countries and companies can stay competitive in an ever-changing digital environment. The authors determine which entrepreneurial processes will work for whom and under what circumstances, presenting methodological implications for business research, start-ups and policy making. Examining the success of Germany as an innovation powerhouse, and comparing this with the USA, this edited collection provides valuable ideas for improving practice, facilitating start-up activity, and ultimately ensuring a country's competitive edge.